Factors associated with clinical deterioration shortly after PE. Issue 9 (20th May 2014) - Kabrhel, Christopher; Okechukwu, Ikenna; Hariharan, Praveen; Takayesu, James Kimo; MacMahon, Peter; Haddad, Faris; Chang, Yuchiao
Abstract : Background: Several factors have been associated with mortality in the months after PE. Factors associated with short-term clinical deterioration or need for hospital-based intervention are less well known. Methods: We prospectively enrolled consecutive emergency department patients with PE and recorded clinical, biomarker and radiographic data. We assessed hospitalised patients daily to identify clinical deterioration or need for hospital-based intervention for 5 days after PE. We captured postdischarge events via 5-day and 30-day interviews. We used univariate and multivariable models to assess associations with clinical deterioration, severe clinical deterioration and 30-day all-cause mortality. We also assessed the test characteristics of three published clinical decision rules. Results: We enrolled 298 patients with PE: mean age 59 (SD±17) years; 152 (51%) male and 268 (90%) white race. 101 (34%) patients clinically deteriorated or required a hospital-based intervention within 5 days, and 197 (66%) did not. 27 (9%) patients suffered severe clinical deterioration and 12 died within 30 days. Factors independently associated with clinical deterioration were hypotension (p=0.001), hypoxia (p<0.001), coronary disease (p=0.004), residual deep vein thrombosis (p=0.006) and right heart strain on echocardiogram (p<0.001). In contrast, factors associated with 30-day all-cause mortality were active malignancy (p<0.001) and congestive heart failure (p=0.009). The sensitivity of clinical decision rules was moderate (39–80%) for 5-day clinical deterioration but higher (67–100%) for 30-day mortality. Conclusions: Most patients do not clinically deteriorate after PE diagnosis. Several factors are associated with short-term clinical deterioration, but these factors differ from those associated with 30-day mortality.